THE CONTRIBUTION OF STATE DEFENSE AND DISCIPLINE PROGRAMS TO STUDENT DISCIPLINE CHARACTER IN POLITEKNIK NEGERI BANDUNG - Siti Samsiyah Purwaningsih; Waway Qodratulloh S; NS Junaedi (Universitas Negeri Medan, 2019)
Abstract: Character education which are carried out in Higher Education is an effort to instill a variety of soft skills that enrich the mastery of students' hard skills. In Polban, various character education programs are developed, two of them are the State Defense Program and Student Discipline Training Program, which are annually carried out in the collaboration with PUSDIKHUB - Indonesian National Army Cimahi. This article describes how the contribution of the State Defense Program and Student Discipline Training Program to the student discipline characters in Polban. The method used is quantitative method, by distributing questionnaires to students before and after participating in the programs. Furthermore, the data from the questionnaire were processed using t-test. The result shows that there is a significant difference between the student discipline attitude in pre-test and the student discipline attitude in post-test. This means that the State Defense Program and Student Discipline Training Program have positive a effect on the student discipline character in Polban. Keywords: character education, state defense program, Contribution. Abstrak: Pendidikan karakter yang dilakukan di Perguruan Tinggi merupakan upaya menanamkan berbagai soft skill yang memperkaya penguasaan hard skill siswa. Di Polban, berbagai program pendidikan karakter dikembangkan, dua di antaranya adalah Program Pertahanan Negara dan Program Pelatihan Disiplin Mahasiswa, yang setiap tahun dilakukan dalam kolaborasi dengan PUSDIKHUB - Tentara Nasional Indonesia Cimahi. Artikel ini menjelaskan bagaimana kontribusi Program Pertahanan Negara dan Program Pelatihan Disiplin Mahasiswa pada karakter disiplin siswa di Polban. Metode yang digunakan adalah metode kuantitatif, dengan menyebarkan kuesioner kepada siswa sebelum dan sesudah berpartisipasi dalam program. Selanjutnya, data dari kuesioner diproses menggunakan uji-t. Hasil penelitian menunjukkan bahwa ada perbedaan yang signifikan antara sikap disiplin siswa pada pre-test dan sikap disiplin siswa pada post-test. Ini berarti bahwa Program Pertahanan Negara dan Program Pelatihan Disiplin Mahasiswa berpengaruh positif pada karakter disiplin siswa di Polban. Kata kunci: pendidikan karakter, program pertahanan negara, Kontribusi